Characterisation of carbonaceous deposits on diesel injector nozzles. (15th August 2020) - McGilvery, Catriona M.; Jiang, Jun; Rounthwaite, Nicholas J.; Williams, Rod; Giuliani, Finn; Britton, T. Ben
Highlights: Nanoscale chemical characterisation of diesel injector nozzle deposits were performed. Deposits from vehicle chassis dynamometer and bench engine based tests are compared. The layer based growth of the deposits are explored revealing chemical stratification. Abstract: Diesel injector nozzles are highly engineered components designed to optimise delivery of fuel into the combustion chamber of modern engines. These components contain narrow channels to enhance spray formation and penetration, hence mixing and combustion. Over time, these injectors can become clogged due to fouling by carbonaceous deposits which may affect the long-term performance of a diesel engine. In this paper we explore the chemical composition and structure of deposits formed within the nozzle at the nanometre scale using electron microscopy. We focus on comparing deposits generated using a chassis dynamometer-based test with Zn fouled fuel with a DW10B dirty up test. We have developed and applied a method to precisely section the deposits for 'top view' scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) analysis of the morphology and relative accumulation of deposits formed during chassis dynamometer and engine based dirty-up tests. We extend this analysis to finer length scales through lift-out of ~70 nm thick electron transparent cross section foils, including both the metal substrate and deposit, using focussed ion beam (FIB) machining. These foils are analysed using scanning transmission electron microscopy (STEM) and STEM-EDS. These thin foils reveal thin-film growth and chemical stratification of Zn, C, O and other elements in the organic deposit layers developed during growth on the steel substrate during industry standard fouling tests.